Mechanisms of Risk Reduction in the Clinical Practice of Alzheimer’s Disease Prevention - Schelke, Matthew W.; Attia, Peter; Palenchar, Daniel J.; Kaplan, Bob; Mureb, Monica; Ganzer, Christine A.; Scheyer, Olivia; Rahman, Aneela; Kachko, Robert; Krikorian, Robert; Mosconi, Lisa; Isaacson, Richard S. (Frontiers in Aging Neuroscience, 2018)
Abstract: Alzheimer’s disease (AD) is a neurodegenerative dementia that affects nearly 50 million people worldwide and is a major source of morbidity, mortality, and healthcare expenditure. While there have been many attempts to develop disease-modifying therapies for late-onset AD, none have so far shown efficacy in humans. However, the long latency between the initial neuronal changes and onset of symptoms, the ability to identify patients at risk based on family history and genetic markers, and the emergence of AD biomarkers for preclinical disease suggests that early risk-reducing interventions may be able to decrease the incidence of, delay or prevent AD. In this review, we discuss six mechanisms—dysregulation of glucose metabolism, inflammation, oxidative stress, trophic factor release, amyloid burden, and calcium toxicity—involved in AD pathogenesis that offer promising targets for risk-reducing interventions. In addition, we offer a blueprint for a multi-modality AD risk reduction program that can be clinically implemented with the current state of knowledge. Focused risk reduction aimed at particular pathological factors may transform AD to a preventable disorder in select cases.